A node‐to‐node scheme with the aid of variable‐node elements for elasto‐plastic contact analysis. (28th January 2015) - Jin, Seungmin; Sohn, Dongwoo; Lim, Jae Hyuk; Im, Seyoung
Summary A strategy for a two‐dimensional contact analysis involving finite strain plasticity is developed with the aid of variable‐node elements. The variable‐node elements, in which nodes are added freely where they are needed, make it possible to transform the non‐matching meshes into matching meshes directly. They thereby facilitate an efficient analysis, maintaining node‐to‐node contact during the contact deformation. The contact patch test, wherein the contact patch is constructed out of variable‐node elements, is thus passed, and iterations for equilibrium solutions reach convergence faster in this scheme than in the conventional approach based on the node‐to‐surface contact. The effectiveness and accuracy of the proposed scheme are demonstrated through several numerical examples of elasto‐plastic contact analyses. Copyright © 2015 John Wiley & Sons, Ltd.